Retinal Thickness Measured by Spectral-Domain Optical Coherence Tomography in Eyes Without Retinal Abnormalities: The Beaver Dam Eye Study - Myers, Chelsea E.; Klein, Barbara E.K.; Meuer, Stacy M.; Swift, Maria K.; Chandler, Charles S.; Huang, Yijun; Gangaputra, Sapna; Pak, Jeong W.; Danis, Ronald P.; Klein, Ronald (American journal of ophthalmology, 2015)
To examine relationships of age, sex, and systemic and ocular conditions with retinal thickness measured by spectral-domain ocular coherence tomography (SD OCT) in participants without retinal disease. Longitudinal study. setting: Population-based cohort. study population: Persons aged 43–86 years living in Beaver Dam, Wisconsin in 1988–1990. observation procedures: Retinal thickness was measured via SD OCT at the Beaver Dam Eye Study examination in 2008–2010. Retinal disease was determined by ophthalmoscopy, fundus photography, or SD OCT. main outcome measures: Retinal thickness from the inner limiting membrane to the Bruch membrane. The retina was thickest in the inner circle (mean 334.5 μm) and thinnest in the center subfield (285.4 μm). Mean retinal thickness decreased with age in the inner circle (P < .0001) and outer circle (P < .0001). Adjusting for age, eyes in men had thicker retinas than eyes in women in the center subfield (P < .001) and inner circle (P < .001). Sex, axial length/corneal curvature ratio, and peak expiratory flow rate were associated with center subfield thickness. Sex and peak expiratory flow rate were associated with retinal thickness in the inner circle. Alcohol consumption, age, axial length/corneal curvature ratio, cataract surgery, ocular perfusion pressure, and peak expiratory flow rate were associated with retinal thickness in the outer circle. This study provides data for retinal thickness measures in eyes of individuals aged 63 years and older without retinal disease. This information may be useful for clinical trials involving the effects of interventions on retinal thickness and for comparisons with specific retinal diseases affecting the macula.